Patent vitellointestinal duct treated during infancy: Case series with literature review (Indian Journal of Case Reports, 2024)
Patent vitellointestinal duct (PVID) is the rarest of all vitelline duct anomalies, resulting from the complete failure of regression of the vitelline duct. Approximately three-fourths of the PVID cases are clinically present during the neonatal period. The present report is a series of three neonates (all boys) operated upon by the author, for the PVID during the study period. All three neonates presented with mucus, flatus, and fecal discharge through the umbilicus. The preoperative diagnosis of PVID was made, due to the classical clinical history and examination findings of fecal/flatus discharges through the umbilicus. All three neonates were operated upon through a sub-umbilical incision. Two neonates underwent resection of the patent duct along with a small adjacent segment of the ileum and ileoileal anastomosis, and one of the neonates underwent a wide wedge resection of the ileum and ileal repair. During the follow-up period, two of the children were doing well. The parents of one of the neonates discontinued the treatment and left the hospital against the medical advice, a week after the operative procedure. Neonates diagnosed with PVID, who mostly presented with fecal discharges through the umbilicus, may also present with the additional features of mucosal/bowel prolapse through the umbilicus.